Analisis Nilai-Nilai Al-Qur’an terhadap Tradisi Assimellereng dalam Konteks Moderasi Beragama di Masyarakat Bugis (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research analyzes the values of the Qur'an in the assimellereng tradition in the Bugis community in relation to Religious Moderation. Assimellereng is a concept of love, togetherness, and unity in the Bugis community to overcome tensions and inter-religious conflicts. This research uses a qualitative method with a review of the Qur'an approach. The main findings show that assimellereng and the teachings of the Qur'an are closely related in building a harmonious and tolerant society. The values of assimellereng, such as sipakatau, sipakalebbi, and sipakainge', align with the principles of religious moderation in the Qur'an. Assimellereng serves as a bridge to build understanding and cooperation among religious communities, as well as to maintain harmony and brotherhood amidst diversity. This research provides a significant contribution to strengthening religious moderation in the Bugis community.